A COMPARATIVE ANALYSIS ON VOCABULARY MASTERY BETWEEN FEMALE AND MALE STUDENTS OF JUNIOR HIGH SCHOOL - Andi Asri Jumiaty (Elite : English and Literature Journal, 2015)
This study was conducted to examine the comparative achievement on English vocabulary mastery between female and male students.The population of this research was all of the second year students of Junior High School which consisted of 300 students and the total sample was 30 students which consisted of 15 female students and 15 male students. The data were collected by using multiple choice tests through analysis descriptive method. The result of the analysis showed that female students and male students have the same vocabulary achievement on vocabulary mastery.